Biosynthesis of Gold Nanoparticles (Green-gold) Using Leaf Extract of Terminalia Catappa - Balaprasad Ankamwar (E-Journal of Chemistry)
The synthesis of eco-friendly nanoparticles is evergreen branch of nanoscience for biomedical application. Low cost of synthesis and non toxicity are main features make it more attractive potential option for biomedical field and elsewhere. Here, we report the synthesis of gold nanoparticles in aqueous medium using Terminalia catappa (Almond) leaf extract as the reducing and stabilizing agent. On treating chloroauric acid solutions with Terminalia catappa (TC) leaf extract rapid reduction of chloroaurate ions is observed leading to the formation of highly stable gold nanoparticles in solution. TEM analysis of the gold nanoparticles indicated that they ranged in size from 10 to 35 nm with average size of 21.9 nm.